Mathematics
yohanaayu79
13

help with number 2 please i have no idea how to do this. it would be very helpful if you can show the steps

+1
(2) Answers
tmosaddegh

Question 2 is -3 You do -2*3 which is -6 and then + 3 so it is -3

Hanington955

y = 3 y = - 2x + 3 sub in 1 y for another 3 = -2x + 3 3 - 3 = -2x 0 = -2x 0 = x....solution is (0,3) =================== y = 3x + 2 y = -3x - 4 sub in 1 y for another 3x + 2 = -3x - 4 3x + 3x = -4 - 2 6x = -6 x = -6/6 x = -1 now sub in -1 for x in either of the original equations to find y y = 3x + 2 y = 3(-1) + 2 y = -3 + 2 y = -1 solution is (-1,-1)

Add answer